Early postnatal morphologic state of the stomach and liver of offspring under conditions of experimental maternal diabetes mellitus (Texas Journal of Multidisciplinary Studies, 2024)
Experimental maternal diabetes mellitus causes inflammatory-dystrophic changes in the vasculartissue structures of the stomach wall and liver of offspring. Morphofunctional disorders of intra-organ vessels of the microcirculatory bed of the organs play a significant role in developing the established pathomorphological disorders of postnatal development of vascular-tissue structures of the stomach and liver in offspring. These disorders then disrupt the trophics of tissue structures and cause dystrophic and degenerative changes